"The obesity paradox" in patients with atrial fibrillation according to the results of the REKUR-AF study - Inna L. Polshakova; Sergey V. Povetkin; Alexey Y. Gaponov (Belgorod National Research University, 2021)
Introduction: to evaluate the effect of excess body weight (EBW) and obesity on the survival of patients with atrial fibrillation (AF) in the REKUR-AF study. Materials and methods: A subanalysis of patients with AF included in the REKUR-AF (382 people) study was performed. Survival rates were analyzed in three patient groups: patients with normal body mass index (BMI), EBW and obesity. Then the nature and significance of the influence of the studied factor on the prognosis in patients with AF were assessed. Results and discussion: Patients with AF and normal BMI were significantly older than those with obesity and EBW (p<0.001 and p=0.021, respectively). Among obese patients, hypertension was significantly (p=0.0015) more common (93.9%) compared to the group of patients with a normal BMI level (80.5%). The frequency of type 2 diabetes in obese patients prevailed over the same indicator in the groups of people with normal BMI and EBW (p=0.007 and p=0.020, respectively). The analysis of the survival rate of patients with AF depending on the BMI level showed that this factor had a significant impact (p=0.013) on the prognosis. The group of individuals with a normal BMI level had a significantly lower survival rate than the cohort of patients with EBW (p=0.011) and OB (p=0.025). The final model for Cox regression analysis (χ2=53.06, p<0.001) included the following factors: age, form of AF, BMI, presence/absence of type 2 diabetes, presence/absence of previous hospitalizations, presence/absence of hypertension, and presence/absence of oral anticoagulant (OAC) intake. Conclusion: The obtained results do not make it possible to unambiguously interpret obesity as a predictor of a positive outcome in this category of individuals.